Manajemen Pendidikan Vokasi Dalam Membentuk Pembelajaran Link and Match Dengan Dunia Industri - Sugiyantoro, Sugiyantoro; Irham, Irham (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
Vocational education management in delivering Indonesian human resources, especially the younger generation, to be able to appear as actors of development, and take part in the international arena. Vocational education has a crucial role in producing human resources (HR) who are ready to face the challenges and opportunities of Industry 4.0. However, there is still a significant gap between the output of vocational education and the real needs of the industrial world, often referred to as the "link and match" problem. This study aims to analyze how vocational education management needs to be transformed to strengthen the link and match with the needs of Industry 4.0. This study uses a qualitative approach. This qualitative approach, to conduct research related to the transformation of vocational education management and its research method using literature review. Data were collected from various relevant scientific literature sources, including national journals, seminar proceedings, books, and research reports that focus on vocational education, education management, Industry 4.0, and the concept of link and match. The results can be concluded that the link and match program is proven by the development of existing programs in schools that can be realized to improve the school's ideals for competition in the industrial world by implementing link and match in several programs, namely (1) Coordination with industry; (2) MoU with industry; (3) Synchronization of curriculum with industry; (4) Industrial work practice; (5) Skills competency test (UKK); (6) Teacher internship; (7) Special Job Fair Program; (8) Teaching factory program, then Link and match will run effectively with neat and proper organization, besides that, it is also inseparable from the supporting factors such as institutional parties, large number of students because it is considered one of the private schools with high trust and productive teaching staff.